Estimasi Komponen Varian Semai Tembesu (Fagraea fragrans Roxb.) pada Umur 6 Bulan - Prastyono Prastyono; Liliek Haryjanto (Universitas Sebelas Maret, 2017)
Tembesu (Fagraea fragrans Roxb.) is one of popular construction woods in South Sumatra due to its strength and durability which are suitable for either indoor or outdoor use. Since tembesu is categorized as slow growth species, no such ultivation has been recorded. The main source of tembesu wood only comes from natural forest which resulted in decreasing tembesu population. To support cultivation of tembesu, a progeny test is required to determine the genetic quality of the mother tree to be used as a seed sources. This study was conducted in the nursery of the Centre for Biotechnology and Tree Improvement Yogyakarta arranged in a Randomized Complete Block Design consisted of 18 families, 5 replicates and 6 treeplots. The research showed that both provenance and family within provenance or mother trees significantly affect the plant growth in term of height and diameter traits. The average of seedling’s height and diameter at age of 6 months was 14.2 cm and 1.8 mm, respectivelly. Estimation of variance components of family for hight and diameter traits were 43.65% and 30.7% of total variance, respectively. The family heritability of height and diameter was estimated to be 0.96 and 0.93 respectively, indicating promising genetic improvement. There is a strong genetic correlation (rg=0.93) between height and diameter traits. These information are important to support tree improvement activities of the species.